Application of T cell receptor (TCR) repertoire analysis for the advancement of cancer immunotherapy. (February 2022) - Joshi, Kroopa; Milighetti, Martina; Chain, Benjamin M
Highlights: TCR repertoire analysis as a tool to advance cancer immunotherapy. Computational methods are used to understand TCR repertoire characteristics. Both TCR sequence and structure have been used for specificity prediction. Abstract : T cell receptor (TCR) sequencing has emerged as a powerful new technology in analysis of the host–tumour interaction. The advances in NextGen sequencing technologies, coupled with powerful novel bioinformatic tools, allow quantitative and reproducible characterisation of repertoires from tumour and blood samples from an increasing number of patients with a variety of solid cancers. In this review, we consider how global metrics such as T cell clonality and diversity can be extracted from these repertoires and used to give insight into the mechanism of action of immune checkpoint blockade. Furthermore, we explore how the analysis of TCR overlap between repertories can help define spatial and temporal heterogeneity of the anti-tumoural immune response. Finally, we review how analysis of TCR sequence and structure, either of individual TCRs or from sets of related TCRs can be used to annotate the antigenic specificity, with important implications for the development of personalised adoptive cellular immunotherapies.